Thinking of Kalam Ulama Aceh XX Century Shaykh Mudawali Al-Khalidi (1917-1961) - Teuku Wildan; Sukiman Sukiman; Amroeni Drajat (Budapest International Research and Critics University, 2019)
This paper tries to review and analyze the thoughts of the twentieth-century Acehnese ulama, Shaykh Mudawali Al-Khalidi, who was one of the charismatic ulama of Aceh in the twentieth century, because in the context of Aceh, the role of a dayah ulama was very influential in people's lives. The problem of kalam thinking that often becomes a hot conversation at any time for example about the acts of servants, the will or justice of God and eschatology, which is believed to be able to answer the problems of the Ummah and there will be a basic concept about it, where the Acehnese people who are known to be harmonious and polite bring many basic foundations kalam that makes them live peacefully. Abuya Mudawali in giving his views on the acts of the servants of God and God gave optional for the servants so that later there would be justice for the servants of God in life after death (eschatology) these three problems are interrelated with each other, then there must be consistency of thought.